Abundance of epiphytic algae on the pneumatophores of Sonneratia alba and Sonneratia caseolaris in the mangrove forest of Lawaan, Eastern Samar - Gular, Giselle C. (2016)
Epiphytic alga is known to be important components of mangrove ecosystems as additional sources of energy. Composition and abundance of epiphytic cyanobacteria on S. alba and S. caseolaris pneumatophores in the mangrove forest of Lawaan, Eastern Samar were studied. Epiphytic alga on Sonneratia alba and Sonneratia caseolaris pneumatophores included Oscillatoria, Lyngbya, Planktothrix, Leptolyngbya, Phormidium, Pseudanabaena, and Johannesbaptistia. Oscillatoria sp., Lyngbya aestuarii, and Planktothrix cryptovaginata were the most prevalent alga observed. Cell densities of L. eastuarii, L. majuscula, O. corakiana, O. vizagapatensis, O. tenuis, and O. vizagapatensis were higher on S. alba while cell densities of O. chilkensis, O. chlorina, O. okeni, O. princeps, and P. cryptovaginata, were higher on S. caseolaris. However, abundance of epiphytic alga was mainly influenced by their tolerance to suboptimal salinity and light intensity conditions, dehydration, and grazing. O. vizagapatensis had the highest mean cell density on S. alba while O. chilkensis had the highest mean density on S. caseoloris with values of 29,369 cells/pn and 70,717 cells/pn, respectively. Alga observed are important nitrogen fixers and biofertilizers in mangrove ecosystems. Therefore, they can significantly help in re-establishing and improving the status of the mangrove forest which was destroyed during super typhoon Haiyan.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and technology